EFFECT OF NITROGEN AND MULCHING ON GROWTH AND YIELD OF PEARLMILLET [PENNISETUM GLAUCUM (L.) R. BR. EMEND. STUNTZ] - VERMA, O.P.; PAREEK, R.G.; PALSANIYA, D. R. (Annals of Agricultural Research, 2014)
A field experiment was conducted during kharif, 2001 at Agronomy farm, SKN College of Agriculture, Jobner (Rajasthan). The treatments comprising of sixteen combinations of four levels each of nitrogen (20, 40, 60 and 80 kg/ha) and mulching (control, dust mulch, mustard straw and Tephrosia purpurea straw) was laid out in a randomized block design and replicated four times. Result indicated that application of 60 N/ ha remaining at par with 80 kg, significantly increased plant height, DM accumulation/m row length and total tillers/plant at 60 DAS and at harvest over 20 and 40 kg N/ha. This treatment also proved superior with respect to number of effective tillers/plant, grain weight/ earhead, grain and straw yield over both the lower levels of nitrogen but the earhead length was significant only over 20 kg N/ha .